Anomalous ferromagnetic behaviour of Y(2)O(3) and CuO nanoparticles in YBa(2)Cu(3)O(y) superconductor - Yanmaz, E; Basoglu, M; Grovenor, C (2009)
Anomalous ferromagnetic behaviour of the Y 2O 3 and CuO components in YBa 2Cu 3O y (Y123) was observed after severe reduction of particle size. The particle size reduction was performed in two ways. First, Y 2O 3, BaCO 3 and CuO were ground for different times to reduce the particle size to the nanoscale. It was found that the superconducting phase could not be obtained without heat treatment, but a weak ferromagnetic behaviour of the mixture was observed at liquid and room temperatures. Second, preheated Y123 powders were subjected to grinding for various times followed by a second sintering process. It was found that the superconducting transition temperature, T c, was strongly suppressed by increasing grinding time, and ferromagnetic behaviour at both room and liquid nitrogen temperatures was also observed. In order to understand which compound is responsible for this weak ferromagnetism, the Y 2O 3, BaCO 3 and CuO powders were separately ground and M-H loops taken at 290K. The resultsindicated that both Y 2O 3 and CuO powders showed weak ferromagnetism, but BaCO 3 showed anti ferromagnetism. It is thought that energy transfer to the powder particles by grinding results in severe plastic deformation of the particles to produce dislocations, vacancies and atomic disorder. We discuss then the observations in the context of recent studies of the magnetic properties of nanoscale oxide materials. © 2009 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.